From The History Of Formation And Development Of Farms In The Republic Of Uzbekistan - Sanjarbek Khamrajonovich Mamajonov (Zien Journals, 2025)
The article provides a scientific analysis of the establishment of farms in the Republic of Uzbekistan during the years of independence, the reforms implemented by the government in the first and second stages of its development and their results on the basis of literature and archival sources.
Keywords: Collective farm; state farm; farm; rent